Harmonic Transfer Function Based Damage Identification of Breathing Cracked Jeffcott Rotor. (6th January 2016) - Zhao, Jie; DeSmidt, Hans; Peng, Meng
Abstract : This paper proposes a vibration-based damage identification method based on 6-dof Jeffcott rotor system, which is based on harmonic balance and Newton-Raphson methods. First, the equations of motion are derived by using energy method and Lagrange principle. The crack model is based on strain energy release rate (SERR) in fracture mechanics and modified to accommodate 6-dof Jeffcott rotor model. Then, Gear's method is used to solve the vibration responses of nominal and damaged rotor systems. By processing vibration responses, the transfer function shifts between nominal and damaged systems are taken as the input of damage identification algorithm. Finally, damage severity can be correlated with the damage parameter estimated via developed damage identification model. Numerical examples are shown to demonstrate the effectiveness in identifying the breathing crack in the rotor system.